A crystallographic and vibrational study of cesium di-μ-aqua bis[tetraaquasodium(I)] decavanadate, Cs₄[Na₂(H₂O)₁₀](V₁₀O₂₈) - Piro, Oscar Enrique (2003)
The title compound crystallizes in the triclinic space group P͞1, with a = 8.6161(4) Å, b = 10.591(1) Å, c = 11.406(1) Å, α = 67.976(7)°, β = 86.868(6)°, γ = 67.798(6)°, and Z = 1. The structure was refined to R1 = 0.0413. The decavanadate anion V₁₀O₂₈⁶⁻ and the [Na₂(H₂O)₁₀]²⁺ bridged cation are located at inversion centers. Partial deuteration of the substance indicates that the coordinated water molecules are strongly asymmetric, forming weak hydrogen bonds with acceptor oxygen atoms from the decavanadate anion. The infrared and Raman spectra are dominated by the water and decavanadate anion bands.